To expand the expression \((-4x - 3)(3x^2 - x - 1)\) and write it in standard form, we will use the distributive property (also known as the FOIL method for binomials):
-
Distribute \(-4x\) to each term in the second parentheses: \[ -4x \cdot 3x^2 = -12x^3 \] \[ -4x \cdot (-x) = 4x^2 \] \[ -4x \cdot (-1) = 4x \]
-
Distribute \(-3\) to each term in the second parentheses: \[ -3 \cdot 3x^2 = -9x^2 \] \[ -3 \cdot (-x) = 3x \] \[ -3 \cdot (-1) = 3 \]
-
Now, combine all these results: \[ -12x^3 + 4x^2 + 4x - 9x^2 + 3x + 3 \]
-
Combine like terms:
- The \(x^2\) terms: \(4x^2 - 9x^2 = -5x^2\)
- The \(x\) terms: \(4x + 3x = 7x\)
-
Therefore, the expression simplifies to: \[ -12x^3 - 5x^2 + 7x + 3 \]
Putting it all together, we have:
\[ \text{Final answer: } -12x^3 - 5x^2 + 7x + 3 \]